Analisis Harga Pokok Penjualan Pada Toko Sinar Kumala Elektronik Di Tenggarong - Astuti, Nini; Iskandar, Iskandar; Sabran, Sabran (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:one of the businesses in Tenggarong is the Sinar Kumala Electronic, which is engaged in the sale of electronic goods such as refrigerators, televisions, air conditioners and others. As for the items contained in the Sinar Kumala Electronic shop originating from the city of Samarinda, Surabaya and Jakarta.Data analysis tool that used to find out the cost of goods sold at the Sinar Kumala Electronic shop in Tenggarong by using inventory and sales data as well as repurchase of goods made. Based on the research note that the hypothesis that has been stated